ADDITION OF SAND IN ARTIFICIAL AQUIFERS TO IMPROVE CLEAN WATER INTO DRINKING WATER - Mohammad Imamuddin (International Journal of Civil Engineering and Infrastructure, 2021)
Water is a very important component for human life. The increasing number of people in Indonesia, such as in the city of Bekasi, will directly result in the demand for clean water for human daily needs getting higher. Quality of water to meet human needs must also be considered. In this case, the Bekasi government through PDAM Patriot Bekasi plays a role in fulfilling water for the needs of its people. However, water from PDAM is only used for clean water needs and cannot be consumed for drinking water. Therefore, this research will provide an alternative so that water is not only used for clean water but also can be used for drinking water by considering existing health standards referring to the Minister of Health Regulation No. 492/MENKES/PER/IV/2010 about drinking water and Minister of Health Regulation No. 416/MENKES/PER/IX/1990 about clean water. The research was carried out by filtration through two (2) samples for testing. The results showed that the use of sand in the filtration method was able to improve quality of PDAM water, both water clarity and color according to regulations as drinking water standards with an arrangement of using medium gravel, coarse sand, red brick, limestone, and fine sand.